PENGARUH UKURAN PERUSAHAAN, UMUR PERUSAHAAN, LEVERAGE DAN UMUR SUKUK TERHADAP PERINGKAT SUKUK (Studi pada Perusahaan yang Menerbitkan Sukuk di Bursa Efek Indonesia) - Widiastuty, Tri (Jurnal Riset Akuntansi, 2017)
Sukuk or Islamic bonds known as one of Islamic financial instruments began to develop at this time. This research was conducted to know the effect of firm size, firm age, leverage, and maturity to sukuk rating simultaneously or partially. This research is expected to give benefit for the development of sharia accounting sciences especially relating to sukuk (Islamic bonds). This research is also expected to give input for company’s management that issued sukuk in determining the factors that affect sukuk rating. This thing can improve or maintain company’s sukuk rating remain high which increase investor trust. The population in this research were the companies that issued corporate sukuk and listed in Indonesia Stock Exchange. The author used the observation data in annual reports from the period 2011 until 2015. Data collection methods used by the author was purposive sampling (data completeness criteria). This research was descriptive research with verificatif approach which was analyzed by using multiple regression analysis. The result of this research was firm size had positive influence to sukuk rating, firm age did not have positive influence to sukuk rating, leverage did not have negative effect to sukuk rating, and age of sukuk had negative influence to sukuk rating.